2021
DOI: 10.4314/jasem.v24i12.6
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of heavy metals from artisanal crude oil refinery (Kpo-Fire) impacted soil using Bacillus flexus and Pseudomonas aeruginosa in Ngie Community, Degema Local Government Area, Rivers State, Nigeria

Abstract: The existence of heavy metals in “kpo-fire” impacted soil creates significant risks to human health and the ecosystem. In this study, the efficacy of the elimination of heavy metal from “kpo-fire” impacted soil was evaluated using bacterial treatments. The organisms (Bacillus flexus and Pseudomonas aeruginosa) used in the bioremediation setup were isolated from the impacted soil. Heavy metal analysis was carried out using an Atomic Absorption Spectrophotometer. The experimental setup involved the recreation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…High presence of nutrients especially carbon, vitamins, fibers (cellulose, hemicelluloses and lignin) and minerals coupled with adequate pH and water tension in dungs, may be the reason for this association. Heterotrophic fungi belonging to the genera Aspergillus, Penicillium, Mucor, Rhizopus, Alternaria, Beauveria, Paeclomyces, and Candida have been found to be dung-loving and to tolerate oilcontaminated environments (Dawodi et al 2015;Ughamba et al 2019). Findings from this work corroborate the report of several workers who found Candida sp., C. tropicalis, Rhizopus sp., Mucor sp., Aspergillus spp., A. niger to be strongly associated with cow and pig dung (Obire et al 2008;Zhou et al 2016;Samuel et al 2017) A wide variety of members of fungal divisions are found on dung; the Mucoromyceta (Zygomyceta) usually appear first, followed by Ascomycota and then the Basidiomycota.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…High presence of nutrients especially carbon, vitamins, fibers (cellulose, hemicelluloses and lignin) and minerals coupled with adequate pH and water tension in dungs, may be the reason for this association. Heterotrophic fungi belonging to the genera Aspergillus, Penicillium, Mucor, Rhizopus, Alternaria, Beauveria, Paeclomyces, and Candida have been found to be dung-loving and to tolerate oilcontaminated environments (Dawodi et al 2015;Ughamba et al 2019). Findings from this work corroborate the report of several workers who found Candida sp., C. tropicalis, Rhizopus sp., Mucor sp., Aspergillus spp., A. niger to be strongly associated with cow and pig dung (Obire et al 2008;Zhou et al 2016;Samuel et al 2017) A wide variety of members of fungal divisions are found on dung; the Mucoromyceta (Zygomyceta) usually appear first, followed by Ascomycota and then the Basidiomycota.…”
Section: Discussionsupporting
confidence: 86%
“…However, chemical reclamation approaches though effective, have been reported to be attended by anthropogenic eutrophication among other shortfalls. Bio-remediation is a technology whereby environmental pollutants are degraded and cleaned up through microbial activity (Akhtar et al 2020;Ugboma et al 2020;Zhang et al 2020). This kind of approach to oil clean-up has the advantages of being non-invasive, rapidacting, cost-effective, eco-friendly and supportive to soil fauna and flora by increasing nutrient availability and uptake by plants (Erdogan et al 2011;Udeani et al 2012;Nwaogu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Holman 32 reported that bacteria failed to grow at low soot concentrations but grew at higher concentrations of the same soot. In agreement with the present study, Ugboma et al 33 reported that microorganisms isolated from soil impacted by artisanal crude oil refining grew well in the presence of heavy metals and were efficient in the elimination of heavy metals from the soil. Soot contains hydrocarbons in low amounts relative to crude oil.…”
Section: Chemical Composition Of Sootsupporting
confidence: 93%
“…Natural geological process, such as ore formation, weathering of rocks, leaching or degassing could introduce heavy metals as contaminant in soil (Gautam et al, 2014;Ali et al, 2019). However, human activities such as illegal refining of fossil fuels, petroleum prospecting, mining, and crude oil pollution can contribute to excessive release of these metals into soils or agricultural lands, resulting in increased concentrations of heavy metals in soil (Okoye et al, 2022;Njoku et al, 2016;Aigberua et al, 2017a;Moslen & Aigberua, 2019;Gwary et al, 2019;Ugboma et al, 2020). In the Ihwrekreka community, identified causes of pollution include illegal refining of crude oil and oil bunkering from pipelines carrying crude oil products (Nwaichi et al, 2016;Ogunkeyede et al, 2022).…”
Section: Introductionmentioning
confidence: 99%